2004
DOI: 10.1038/sj.gene.6364093
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association between juvenile rheumatoid arthritis and polymorphism in the SH2D2A gene

Abstract: T-cell-specific adapter protein (TSAd) involved in the negative control of T-cell activation is encoded by the SH2D2A gene. Our recent studies indicate that homozygosity for short (ie GA 13 and GA 16 ) alleles of the SH2D2A gene promoter is associated with development of multiple sclerosis. To study whether the same SH2D2A promoter polymorphism also contributes to the genetic susceptibility to develop juvenile rheumatoid arthritis (JRA), we examined 210 JRA patients and 558 healthy unrelated controls from Norw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 16 publications
(45 reference statements)
2
12
0
1
Order By: Relevance
“…Also upstream of ZAP-70 is T cell-specific adaptor (TSAd), required for optimal activation of ZAP-70 by LCK (Marti et al, 2006). A promoter polymorphism in the gene encoding TSAd, SH2D2A, is associated with multiple sclerosis and juvenile rheumatoid arthritis (Dai et al, 2001;Smerdel et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Also upstream of ZAP-70 is T cell-specific adaptor (TSAd), required for optimal activation of ZAP-70 by LCK (Marti et al, 2006). A promoter polymorphism in the gene encoding TSAd, SH2D2A, is associated with multiple sclerosis and juvenile rheumatoid arthritis (Dai et al, 2001;Smerdel et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This reduction in available IL-7 in turn reduces thymic output of T cells (Broux et al 2010), replicating on a less severe form the immunological defect present in Omenn syndrome. Similarly, the gain-of-function PTPN22 allele associated with multiple autoimmune diseases results in a reduction in T-cell receptor (TCR) signaling (Smerdel et al 2004;Vang et al 2005), and may therefore also contribute to partial immunodeficiency.…”
Section: Common Autoimmune Risk Variantsmentioning
confidence: 99%
“…Promoter sequences that include at least two GA-elements are necessary for nucleosome displacement when GAGA is competing directly with the nucleosome assembly reaction, and sequences including three to four elements are required for the disruption of a preassembled nucleosome (Tsukiyama et al, 1994;Brasset and Vaury, 2005). Involvement of promoter GA-repeats in complex disorders has been reported by several groups (Morris et al, 2010;Notturno et al, 2008;Smerdel et al, 2004). It has been shown that individual differences in gene expression patterns may be conferred via polymorphic microsatellites in the cis-regulatory regions of genes and may contribute to normal variation in behavioral traits (Hammock and Young, 2005).…”
Section: Discussionmentioning
confidence: 96%